Persiapan Guru Dalam Melaksanakan Sistem Pembelajaran Merdeka Belajar Pada Tingkat Sekolah Dasar - Cindy Sinomi; Adisel Adisel; Fatrima Santri Syafri (Yayasan Darusssalam Bengkulu, 2021)
This research was carried out with the aim of knowing Teacher Preparation in Implementing an Independent Learning System at SD N 01 Muara Pinang, Muara Pinang District, Empat Lawang Regency, South Sumatra Province. The learning system